HUBUNGAN PENGUASAAN KALIMAT EFEKTIF DAN KECERDASAN INTERPERSONAL DENGAN KETERAMPILAN MENULIS TEKS PERSUASI SISWA KELAS VIII SMPN 26 KOTA TANGERANG - Fahmi Hafidatul Hidayati; Suprani Suprani; Tatu Hilaliyah (Jurnal Membaca Bahasa dan Sastra Indonesia, 2019)
This study aims to determine information whether or not relationship between effective sentence mastery and interpersonal intelligence together with writing skills of persuasive text of VIIIth grade of SMP 26 Kota Tangerang. This research includes the type of quantitative correlation research. The population are 306 students and sample are 60 students. The first requirement test result, the data normality test obtained the level of significance for the variable X1, X2, and Y the data comes from a population of the normal distribution, at a significant level of 0.05. The second prerequisite test is the linearity test (X1) with (Y) of 0.300, (X2) with (Y) is 0.954. From the calculation of multicollinearity test obtained tolerance of variables X1 and X2 that is 0.654 greater than 0.10. Meanwhile, VIF (Variance Inflation Factor) values of variables X1 and X2 are smaller than 10.00. So it can be concluded not to happen multicollinarity. The results of analysis show that (1) there is a significant relation between effective sentence mastery with writing skill of persuasive text of rhitung (0.607) > rtable (0.254) at the 0.05 correlation coefficient tested its significance by looking at price t, where thitung (8.513) > of ttable (2.002); (2) there is significant relatio between interpersonal intelligence with writing skill of and persuasive text, of rhitung (0.498) > rtable (0.254) at the 0.05 significance level, correlation coefficient is tested its significance by looking price t, where thitung (4.376) > ttabel (2,002); (3) there is a significant correlation between mastery of effective sentence and interpersonal intelligence together with writing skill of persuasive text (1,2) equal to 0.640, significant correlation coefficient with F-test obtained Fhitung = 19.762 at the real level 0.05 with df numerator 2 and df denominator 57 obtained Ftable at 3.16 then Fhitung> Ftable. The result of the study indicate that effective sentence mastery contributes significantly to the results of writing skills of persuasive is 36.8%, interpersonal intelligence is 24.8%, while effective sentence mastery and interpersonal intelligence together can influence 40.9% changes in writing skills of persuasive (Y) which means better together.